Redevelopment of a manufacturing factory in an energy generation plant with wood biomass - Cefalo, Raffaela (Geodetski vestnik, 2023)
A manufacturing company, which uses obsolete processes and technologies, due to the economic crisis, is evaluating a possible conversion to the energy sector. The paper presents a careful analysis of local resources in the mountain area of Carnia (Italy), identifying the available wood biomass, using Geographic Information System (GIS) instruments. The biomass can be exploited in energy generation plants and represents, a good option with a high margin of profit and takes advantage of the district heating technology. The technical feasibility also used numeric regional cartography to assess the energy needs, while the economic feasibility is highly influenced by local regulations on public incentives, established to reach the environmental goals set by the international treaties. On the other hand, the environmental sustainability of these plants is often positive, even if related to the local context. The consequent reduction of CO2 emissions is relevant, as long as the location of the boiler room is correctly identified in order to optimize the supply chain from the forests to the plant.
Keywords: cogeneration; daljinsko ogrevanje; district heating; GIS; lesna biomasa; soproizvodnja; sustainability; trajnost; wood biomass